Family functioning and quality of life among children with anxiety disorder and healthy controls. A cross-sectional study - Öztürk, Yusuf; Özyurt, Gonca; Akay, Aynur (São Paulo Medical Journal, 2018)
BACKGROUND: Studies have shown that children with anxiety disorders (ADs) present impaired family functioning and quality of life. We aimed to evaluate family functioning and quality of life among children with AD and healthy controls. DESIGN AND SETTING: Cross-sectional study (survey) at two centers in Turkey. METHODS: The study group comprised 42 children diagnosed with AD and 55 controls. The Screen for Child Anxiety-Related Emotional Disorders (SCARED) questionnaire was filled out by their parents to measure the severity of anxiety symptoms. Family functioning among the children was assessed using the Family Assessment Device (FAD) and Parental Attitude Research Instrument (PARI). The children’s quality of life was assessed through the Pediatric Quality of Life Inventory (PedsQL). RESULTS: The children’s average age was 10.00 ± 0.21 years in the AD group and 9.98 ± 1.53 years among the controls. There were higher scores on all FAD subscales in the AD group (2.15 ± 0.52; 2.29 ± 0.44; 2.44 ± 0.55; 2.10 ± 0.61; 2.56 ± 0.40; 2.32 ± 0.33; and 2.29 ± 0.47). On PARI subscales, there were significant differences favoring the AD group (p < 0.05), except for democratic attitude. All PedsQL subscales differed significantly between the groups, favoring the AD group. A statistically significant relationship was found between all PedsQL subscales and SCARED scores in the AD group. CONCLUSION: We found that both family functioning and quality of life among children with AD were negatively affected. However, further studies with larger sample sizes are required to reach stronger conclusions.